Socially cued smoking in bars, nightclubs, and gaming venues: a case for introducing smoke-free policies. Issue 4 (1st December 2002) - Trotter, L; Wakefield, M; Borland, R
Abstract : Objective: To assess smokers' perceived effects of smoking bans in bars, nightclubs, and gaming venues on their smoking behaviour. Design: Cross sectional structured interview telephone survey of a random sample of smokers. Setting: Population survey in Victoria, Australia. Participants: The sample comprised 597 smokers and analyses were conducted on 409 smokers who reported patronising bars, nightclubs or gaming venues at least monthly. Outcome measures: Two outcomes studied were socially cued smoking and readiness to quit as a result of restrictions on smoking in social venues. Respondents were identified as socially cued smokers if they reported attending bars, nightclubs or gaming venues at least monthly and said that they smoke more in these venues. The potential influence of bans in social venues on readiness to quit was measured by asking respondents if they would be more or less likely to quit smoking if smoking were banned in hotels, licensed bars, gaming venues, and nightclubs. Results: Of all adult smokers, 69% attended bars, nightclubs or gaming venues at least monthly. Of these smokers, 70% reported smoking more in these settings (socially cued smokers) and 25% indicated they would be likely to quit if smoking were banned in social venues. Compared to smokers not likely to quit if there were bans, smokers likely to quit were more likely to be socially cued (odds ratio (OR) 2.64), to be contemplating or preparing to quit (OR 2.22), to approve of bans in social venues (OR 2.44), and to be aged under 30 years (OR 1.73). Compared with smokers not socially cued, socially cued smokers were more likely to be under the age of 30 years (OR 6.15), more likely to believe that there is a safe level of cigarette consumption (OR 2.25), and more likely to have previously made a quit attempt (OR 2.60). Conclusions: These findings suggest that bans on smoking in bars, nightclubs, and gaming venues could reduce cigarette consumption and increase quitting among smokers who frequently patronise these settings. These beneficial effects are likely to be strongest among younger smokers.